Synthesis of MFe2O4 (M=Mg2+, Zn2+, Mn2+) spinel ferrites and their structural, elastic and electron magnetic resonance properties. Issue 9 (15th June 2018) - Prasad, S.A.V.; Deepty, M.; Ramesh, P.N.; Prasad, G.; Srinivasarao, K.; Srinivas, Ch.; Vijaya Babu, K.; Ranjith Kumar, E.; Krisha Mohan, N.; Sastry, D.L.
Abstract: Structural, elastic and electron magnetic resonance investigations of spinel ferrites with the formula MFe2 O4 (M = Mg 2+, Zn 2+, Mn 2+ ) synthesized by the sol-gel auto-combustion method are reported here. XRD patterns revealed the co-existence of secondary phases along with the ferrite phase. The lattice parameter (8.301 Å, 8.366 Å and 8.434 Å) was found to be varying according to the ionic radii of cations. As determined by scanning electron microscopy (SEM), ZnFe2 O4 has a comparatively narrow distribution of grain sizes (1.3–3.8 µm) compared to those in MnFe2 O4 (0.8–4.3 µm) and MgFe2 O4 (0.3–4.8 µm). The estimated values of average crystallite sizes (17.5 nm, 21.3 nm and 23.3 nm) determined from the X-ray diffraction peaks are considerably less than the average grain sizes (1.3 µm, 1.6 µm and 2.7 µm) estimated from the SEM histograms. The vibrational frequencies in FTIR spectra are in the conformity with the cubic spinel structure and their variation supports the variation of lattice parameter. Equal values of Poission's ratio (0.35) were obtained for the three systems which represent the isotropic behaviour of spinel ferrite systems. The exceptional low value of Lande's g -parameter for ZnFe2 O4 indicates the dominance of Fe 3+ –O–Fe 3+ superexchange interaction. Though cation redistribution is possible in the present ferrite systems, the secondary phases existed in these ferrite systems are predominantly influencing the structural, elastic and electron magnetic resonance properties.